(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2012)
This essay proposes a cognitive model of aesthetic emotions. Their nature, forms, functions are explained on the basis of empirical and theoretical results of neurocognitive sciences about ordinary emotions, integrated with concepts selected from aesthetics. The proposed explanation confirms the essential role of aesthetic emotions in cultural learning and creation, dissolving the paradox of fiction.